Smart beta investing: A comparative study of fundamental accounting metrics and traditional market capitalization indices to measure the performance of the Philippine Stock Exchange - Argamosa, Miguel Benedicto Ramirez (Animo Repository, 2023)
Amidst a dynamic and ever-evolving financial landscape, investors and financial analysts are continuously exploring alternative investment strategies to enhance portfolio performance and mitigate risks. Due to the nature of the program that the authors are taking, they have been showing a keen interest in evaluating the profitability of portfolios. Whether the Philippine Stock Exchange Index (PSEi) provides a sufficient baseline for comparison has been a persistent question. Due to this, a potential alternative benchmark has evolved as a result of the introduction of fundamental indices in the Philippines, which were accompanied by claims that they were superior to the traditional market capitalization-weighted (MCW) index. Hence, the objective of this study is to evaluate the performance of fundamental indices based on accounting metrics on the Philippine Stock Exchange (PSE) between 2014 to 2020. Specifically, assessing the absolute, relative, and risk-adjusted returns of these indices in comparison to the PSEi. The study found that fundamental indices as applied to the top 31 stocks failed to deliver overperformance compared to the PSEi from 2014-2020. To add, utilizing a regression analysis, the study also revealed that the Fama-French model together with APT variables (proxied by ROE, ROA, EPS, PER) failed to statistically explain the variations of the returns of the fundamental indices. Results show that Market Risk Premium, as reflected in CAPM, is a simple yet relevant model that can be used to estimate and ascertain future returns. Lastly, the empirical investigation done in this study implies that fundamental indices as an alternative investment strategy are not guaranteed to overperform and that the other financial metrics not examined may signify that it may or may not explain the variation of investment returns.